Proton-activated chloride channel PACC1 as acid sensor in epidermal desquamation - Keyu Xia; Xiangjian Liu; Jiajing Wu; Junyan Hu; Xufeng Cheng; Tingyan Mi; Bomin Gao; Xiaoyi Mo; Xuteng Lu; Feng Cao; Chang Xie; Jian Cao; et al. (Proceedings of the National Academy of Sciences, 2026)
The acidic microenvironment of the stratum corneum is crucial for epidermal desquamation and barrier homeostasis, yet the primary proton sensor that triggers this process remains unknown. Here, we report that the proton-activated chloride channel PACC1 is essential for acid-induced upregulation of kallikreins (KLKs) and desmosomal degradation, two key steps in skin exfoliation. Functional and protein expression analyses revealed that PACC1 is the predominant acid-sensitive ion channel in keratinocytes. Proton-mediated PACC1 activation evokes chloride efflux and initiates a signaling cascade via the c-Jun N-terminal Kinase/AP-1 (JNK/AP-1) pathway. This cascade significantly enhances the expression and secretion of KLKs (KLK5/7), thereby facilitating desquamation through corneodesmosomal degradation. Notably, acid-induced KLK upregulation was abolished by PACC1 knockdown, knockout, or mutants that are deficient in proton sensing. This effect was also observed with pharmacological channel inhibition and was specifically restored by reconstitution with functional PACC1. These findings establish PACC1 as the core sensor that converts epidermal acidification into a desquamation signal, providing a mechanistic foundation for developing targeted therapeutic and cosmetic strategies that modulate skin barrier function.